The Effectiveness of E-LKPD on Environmental Pollution Material Based on PBL (Problem Based Learning) to Improve Students’ Critical Thinking Skills - Sari, Nanda Devita; Isnaeni, Wiwi; Ellianawati, Ellianawati (Unnes Science Education Journal, 2024)
Global challenges and competition require quality human resources to compete in society with 21st century skills. Critical thinking skills are competencies to be able to solve problems needed to answer challenges in the present and the future. The use of E-LKPD based on problem based learning (PBL) on environmental pollution material is very influential in triggering critical thinking. The purpose of this study was to analyze the effectiveness of the use of E-LKPD based on problem based learning (PBL) for students' critical thinking skills with biology learning activities on environmental pollution material. This study is a quantitative study using a quasi-experimental method. The results of the effectiveness of E-LKPD on students' critical thinking skills were obtained from the results of the N-gain analysis, it is known that the N-gain value in the experimental class is much higher with an N-gain value of 0.69 with moderate criteria, while the N-gain value in the control class is 0.37 with moderate criteria. The N-Gain test shows that the N-Gain value of the experimental class is greater than the control class. Therefore, E-LKPD based on problem based learning (PBL) on environmental pollution material is effective in improving students' critical thinking skills in learning.